Synthesis of pogostone by one-step. Issue 2 (1st February 2017) - Chen, Han-Bin; Zhou, Jiang-Tao; Liu, Yu-Hong; Zhang, Zhen-Biao; Zhan, Ya-Xian; Su, Zi-Ren; Zeng, Hui-Fang
Abstract: Pogostone, isolated from Pogostemon cablin, has many biological activities such as potential antibacterial, anticandida, and antifungal. Traditional extraction leads to low output of PO about 17.6 mg/kg from Herba Pogostemonis. The previous literature had reported a synthetic study and the yield had reached 4.48% with strictly controlled reaction conditions. The two methods above cannot meet the large demand of PO; we report a new synthesis method. 4-hydroxy-6-methyl-2-pyrone (1) was added in toluene, with the existence of acylation catalyst 4-dimethylaminopyridine (DMAP), 4-methylvaleric acid (2), and condensing agent dicyclohexylcarbodiimide (DCC), PO was synthesized after the combination of 3-carbon of (1) with 1-OH of (2) in the acylation reaction. The purity had reached 98%, determined by HPLC. The structure was confirmed by spectroscopic methods including infrared, electron ionization mass spectrometry, and nuclear magnetic resonance spectroscopy. PO was totally synthesized in one step including cyclization, with total yield of 27.2%.